2012
DOI: 10.1038/ki.2011.499
|View full text |Cite
|
Sign up to set email alerts
|

The kallikrein–kinin system in diabetic nephropathy

Abstract: Diabetic nephropathy is the major cause of end-stage renal disease worldwide. Although the renin-angiotensin system has been implicated in the pathogenesis of diabetic nephropathy, angiotensin I-converting enzyme (ACE) inhibitors have a beneficial effect on diabetic nephropathy independently of their effects on blood pressure and plasma angiotensin II levels. This suggests that the kallikrein-kinin system (KKS) is also involved in the disease. To study the role of the KKS in diabetic nephropathy, mice lacking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 149 publications
2
37
0
2
Order By: Relevance
“…Beyond a role in blood pressure lowering, bradykinin acting via its receptors may also play a role in modifying kidney injury in diabetes. For example, studies in mice lacking bradykinin receptors show that they have dramatic acceleration of albuminuria and glomerular pathology, indicating a protective effect of bradykinin in diabetic nephropathy (164-167, 361). These studies suggest that ACE activity has the potential to modulate renal disease in diabetes via degradation of bradykinin, and that one potential mechanism underlying the benefits of ACE inhibition in diabetic nephropathy (207, 209) might be potentiation of bradykinin effects.…”
Section: Angiotensin Converting Enzymementioning
confidence: 99%
“…Beyond a role in blood pressure lowering, bradykinin acting via its receptors may also play a role in modifying kidney injury in diabetes. For example, studies in mice lacking bradykinin receptors show that they have dramatic acceleration of albuminuria and glomerular pathology, indicating a protective effect of bradykinin in diabetic nephropathy (164-167, 361). These studies suggest that ACE activity has the potential to modulate renal disease in diabetes via degradation of bradykinin, and that one potential mechanism underlying the benefits of ACE inhibition in diabetic nephropathy (207, 209) might be potentiation of bradykinin effects.…”
Section: Angiotensin Converting Enzymementioning
confidence: 99%
“…Recent studies have found that the KKS could significantly inhibit glomerulosclerosis (Schanstra et al, 2002;Marceau and Regoli, 2004;Kakoki et al, 2004;Tan et al, 2005;Tomita et al, 2012). The kidney contains various components of KKS, and bradykinin (BK), the most important bioactive peptide of KKS, is the final effector exerting the effects described above.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies [28][29][30][31] show that deletion of B1R and B2R exacerbates the renal phenotype in diabetic mouse models, suggesting that both receptors have a protective effect on diabetic nephropathy by suppressing oxidative stress via NO and prostaglandins. However, because the absence of one of the receptors causes increased expression of the other, it is difficult to determine the precise function of each receptor [28] .…”
mentioning
confidence: 99%
“…However, because the absence of one of the receptors causes increased expression of the other, it is difficult to determine the precise function of each receptor [28] . In other models, such as the I/R model [15] the receptors' role was also studied.…”
mentioning
confidence: 99%
See 1 more Smart Citation